The Impact of the Non-Cash Food Assistance (BPNT) Program on Household Welfare in Indonesia - Meriska Suwatri; Hefrizal Handra; Efa Yonnedi (Transpublika Publisher, 2024)
One of the government’s steps to address poverty through food security is the launch of the Non-Cash Food Assistance (BPNT) program. This study evaluates the impact of the Non-Cash Food Assistance (BPNT) program on household welfare in Indonesia. Utilizing logistic regression analysis and data from the 2017 National Socio-Economic Survey, the research reveals that participation in the BPNT program has a significant negative effect on household welfare. Recipients of BPNT are 8.366% less likely to achieve prosperity compared to non-recipients. This outcome underscores the need to address additional factors influencing welfare, such as education, employment opportunities, and access to social services. While the BPNT program effectively provides food assistance, its design and implementation require improvements to better support recipients in overcoming economic challenges. Enhancing the program's scope and efficiency is essential for achieving its objective of sustainable poverty alleviation and improving welfare outcomes for vulnerable households in Indonesia.